Antioxidant enzyme profile and lipid peroxidation products in semen samples of testicular germ cell tumor patients submitted to orchiectomy - Sposito,Camila (2017)
ABSTRACT Purpose To determine enzymatic antioxidant and lipid peroxidation levels in seminal plasma of patients orchiectomized for testicular tumors. Materials and Methods The study included 52 patients: 26 control men and 26 orchiectomized patients for testicular tumor, of which 12 men had seminoma tumor and 14 men non-seminoma tumor. After semen analysis performed according to the WHO guidelines, an aliquot of semen was centrifuged and the seminal plasma was collected. Lipid peroxidation was performed by thiobarbituric acid reactive substances (TBARS) assay and antioxidant profile was assessed by analyzing catalase, glutathione peroxidase (GPx) and superoxide anion (SOD) activities using colorimetric assays with a standard spectrophotometer. Data were tested for normality and compared using one-way ANOVA (p<0.05). Results Seminoma and non-seminoma groups presented lower sperm concentration and morphology when compared to control group (p=0.0001). Both study groups (seminoma and non-seminoma) presented higher TBARS levels when compared to control group (p=0.0000013). No differences were observed for SOD (p=0.646) andGPx (p=0.328). It was not possible to access the enzymatic activity of catalase in any group. Conclusion Patients with testicular tumor present increased semen oxidative stress, but no differences were observed in antioxidant levels, even after orchiectomy. This indicates that most likely an increased generation of oxidative products takes place in these patients.